(untitled) (Revista Educação, Artes e Inclusão, 2021)
The inclusion of a person with disability in the Professional and Technological Education (EPT) is the theme of this study – part of a master’s research – and has as objective to analyze how students with disability understand the inclusion process in the technical courses of the Professional Education Center (CEFORES), atechnical school linked to Federal University of Triângulo Mineiro (UFTM), which offers professional education, mainly in the health area, since 1990. The investigation is also characterized by: a) understanding how the coexistence is among students with disability, teachers and classmates; b) identifying if students consider that their demands are assisted and c) knowing these students’ expectations after the professional formation. This study presents a qualitative approach of exploratory and descriptive character. It was used a semi-structure guideline interview as procedure for collecting data and it was analyzed through thematic analysis. The research understood that besides the support of a specialized education it is also importante that teachers have a continued formation, with intention of supplying the students with disability a solid formation.